2003
DOI: 10.1002/chem.200304808
|View full text |Cite
|
Sign up to set email alerts
|

Selective Recognition of Configurational Substates of Zinc Cyclam by Carboxylates: Implications for the Design and Mechanism of Action of Anti‐HIV Agents

Abstract: The interaction of metal cyclams with carboxylate groups is thought to play an important role in their binding to the CXCR4 chemokine receptor and in their anti-HIV activity. Here we report the synthesis of acetate, phthalate, perchlorate and chloride complexes of Zn(II) cyclam (1,4,8,11-tetraazacyclotetradecane). The X-ray crystal structures of [Zn(cyclam)(phthalate)](n)(CH(3)OH)(2n) and [Zn(cyclam)(H(2)O)(2)](OAc)(2) contain octahedral Zn(II) centres. Phthalate acts as a bridging ligand in the former complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 32 publications
(24 reference statements)
9
77
0
Order By: Relevance
“…Despite repeated efforts utilizing several chromatographic techniques, these isomers were not separable, possibly due to kinetic lability of the bound metal ion. It has been previously observed 34 that crystallized Zn(II) complexes of the structurally related cyclam macrocycle, with a known configuration of N-donors, rapidly isomerize to give an equilibrium distribution when redissolved, and it is likely that a similar situation applies in this case. As such, the decay behavior of both Zn(II) complexes is in accord with the 1 H NMR Zn(II) complexation titrations, which demonstrated the appearance of two differing methylene linker resonances.…”
Section: ∆G°(ev) ) E°(dmentioning
confidence: 94%
“…Despite repeated efforts utilizing several chromatographic techniques, these isomers were not separable, possibly due to kinetic lability of the bound metal ion. It has been previously observed 34 that crystallized Zn(II) complexes of the structurally related cyclam macrocycle, with a known configuration of N-donors, rapidly isomerize to give an equilibrium distribution when redissolved, and it is likely that a similar situation applies in this case. As such, the decay behavior of both Zn(II) complexes is in accord with the 1 H NMR Zn(II) complexation titrations, which demonstrated the appearance of two differing methylene linker resonances.…”
Section: ∆G°(ev) ) E°(dmentioning
confidence: 94%
“…It is known that only the trans-I and trans-III configurations give rise to three pairs of signals in the 2D [ 1 H, 13 C] HSQC spectrum, therefore Ni II cyclam acetate must adopt one of these configurations. [11] Since squareplanar Ni II is a better fit for the cavity in trans-I cyclam, it is concluded that diamagnetic Ni II cyclam adopts the trans-I configuration in the present case.…”
Section: X-ray Crystallographymentioning
confidence: 58%
“…[10] It has been shown that trans-III complexes of zinccyclam complexes (with acetate, phthalate, perchlorate or chloride as counterions) equilibrate over a period of hours to form mixtures of cis-V, trans-I and trans-III isomers. [11,12] Acetate, in particular, can induce formation of the cis-V configuration, and the most prominent adduct of Zn II 2 -xylylbicyclam in the presence of acetate adopts cis-V/trans-I configurations. [12] Metal complexes of xylylbicyclam appear to bind to the carboxylate groups of Asp262, Glu288 and Asp171 of CXCR4.…”
Section: Nia C H T U N G T R E N N U N G (Cyclam)-a C H T U N G T R Ementioning
confidence: 99%
See 2 more Smart Citations